An Ultrastable 155‐Nuclei Silver Nanocluster Protected by Thiacalix[4]arene and Cyclohexanethiol for Photothermal Conversion. (15th June 2022) - Wang, Zhi; Alkan, Fahri; Aikens, Christine M.; Kurmoo, Mohamedally; Zhang, Zhen‐Yi; Song, Ke‐Peng; Tung, Chen‐Ho; Sun, Di
Abstract: Thiacalix[4]arenes have emerged as a family of macrocyclic ligands to protect metal nanoparticles, but it remains a great challenge to solve the mystery of their structures at the atomic level, especially for those larger than 2 nm. Here, we report the largest known mixed‐valence silver nanocluster [Ag155 (CyS)40 (TC4A)5 Cl2 ] (Ag155 ) protected by deprotonated cyclohexanethiol (CySH) and macrocyclic ligand p ‐ tert ‐butylthiacalix[4]arene (H4 TC4A). Its single‐crystal structure consists of a metallic core of four concentric shells, Ag13 @Ag42 @Ag30 @Ag70, lined with a organic skin of 40CyS − and 5TC4A 4− and 2Cl − . Ag155 manifests an unusual pseudo‐5‐fold symmetry dictated by the intrinsic metal atom packing and the regioselective distribution of mixed protective ligands. This work not only reveals a macrocyclic ligand effect on the formation of a large silver nanocluster, but also provides a new structural archetype for comprehensively perceiving their interface and metal kernel structures. Abstract : An unusual C 5h ‐symmetric silver nanocluster (Ag155 ) with the highest reported nuclearity was prepared by exploiting the protection of the macrocyclic ligand p ‐ tert ‐butylthiacalix[4]arene (H4 TC4A) and cyclohexanethiol (CySH). This silver nanocluster exhibits excellent stability in solution and photothermal conversion efficiency.